Mites of the order Mesostigmata on plots reforested with Scots pine after various kinds of soil preparation and wood residue utilization after clear-cutting - Skorupski, Maciej; Gornowicz, Roman; Spaeth, Marcin; Wierzbicka, Anna (Biological Letters, 2011)
The clear-cutting system is still popular, especially on poor sites in Central European forests. It causes serious disturbances in natural processes during forest regeneration. The main objective of this research on mesostigmatid mites was to evaluate and compare the influence of various kinds of soil preparation and treatment of the wood debris left after clear-cutting (on plots reforested with Scots pine Pinus sylvestris). As a result of the conducted investigations, 24 mite species of the order Mesostigmata were found. The highest number of species represented the families Parasitidae (7 species), Laelapidae (4 species) and Zerconidae, Digamasellidae, Ascidae (3 species each). The study was conducted on an experimental plot in the Międzychód Forest District (West Poland). The species composition of mite communities on all subplots is characteristic for Scots pine forests. The highest numbers of individuals and species were collected on the plots where the wood residue was burnt or chipped and left on the soil surface. The lowest numbers of individuals and species were colleted on the plots where the chipped wood residue was mixed with soil or removed from the plots. The method of wood residue utilization significantly influenced the community structure of the Mesostigmata, while various kinds of soil preparation before reforestation did not have any significant influence.